2022
DOI: 10.1097/md.0000000000029144
|View full text |Cite
|
Sign up to set email alerts
|

Perihippocampal failure after hippocampal-avoidance whole-brain radiotherapy in cancer patients with brain metastases

Abstract: Perihippocampal failure is a rare clinical scenario in brain metastatic cancer patients following hippocampal-avoidance (HA) whole-brain radiotherapy (HA-WBRT). The clinical features have not been fully identified because clinical data on intracranial failure after HA-WBRT are limited. It is thus necessary to accumulate clinical data.We retrospectively analyzed cancer patients with brain metastases who were diagnosed between January 2014 and September 2020 at a regional referral hospital. The medical records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Following these prospective clinical trials to confer neuro-cognitive protection in metastatic brain disease, HA-WBRT has gained clinical acceptance (7,8). However, perihippocampal failure has been reported from clinical observations (18)(19)(20). We have also reported unusual cases of intracranial failure following HA-WBRT therapy and perihippocampal failure rate was about 8% in…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Following these prospective clinical trials to confer neuro-cognitive protection in metastatic brain disease, HA-WBRT has gained clinical acceptance (7,8). However, perihippocampal failure has been reported from clinical observations (18)(19)(20). We have also reported unusual cases of intracranial failure following HA-WBRT therapy and perihippocampal failure rate was about 8% in…”
Section: Discussionmentioning
confidence: 89%
“…our previous report (18). RTOG 0933 recommended stringent dose criteria which required a high dose homogeneity and precise radiation delivery.…”
Section: Discussionmentioning
confidence: 96%
“…Hippocampal contouring and HA-WBRT planning directives of 3 cases were guided by the RTOG 0933 criteria, [10] and the technique and clinical study are described in our previous study. [14,15] To investigate whether a deviation of underdose in the HA region led to perihippocampal failure, we assessed the parameters of dosimetry in the HA-WBRT planning of our cases (Table 1). We compared the brain dose of patients A to C and the underdose region around the HA region by maping the MRI scans of intracranial failure and previous planning CT scan of simulation and found that a deviation of the underdosed region within the perihippocampal failure was approximately 55% to 63%.…”
Section: Dosimetric Analysis Of Hippocampal Failurementioning
confidence: 99%